Handbook of socialization theory and research - Grusec, Joan E.; Hastings, Paul D. (Paul David) 1966- (The Guilford Press, 2015)
"Socialization refers to the way in which individuals are assisted in becoming members of one or more social groups, including how the newer members as well as the established ones socialize one another, often in a bi-directional manner, that is, response to socialization impact in both directions. This is the only handbook on socialization that covers the topic from infancy through adulthood. Hot new topics include moral development; the media as a socializing agent; behavior genetics; and, culture. Authors are known in the field"--Provided by publisher.